Etika dan Desain Kerja Berpusat pada Manusia dalam Integrasi AI pada Ekosistem Platform Industry 5.0 - Miftahurroziqin, Miftahurroziqin; Wardhani, Dyah Febria; Mulyawan, Rifqi (Jurnal Sosioteknologi, 2025)
This study proposes a conceptual-analytical framework for human-centric AI integration in Industry 5.0 by employing a Systematic Literature Review (SLR) and Applied Framework Analysis (AFA). A structured PRISMA-based screening process was applied to ensure transparency in identifying and selecting 48 scholarly sources that inform the framework. The review reveals three foundational dimensions enabling responsible AI adoption: ethical governance grounded in transparency and accountability, inclusive innovation addressing bias and digital inequality, and futureready human capital oriented toward capability enhancement. These dimensions are synthesized into a sociotechnical framework that bridges normative humancentric principles with organizational practice. To demonstrate its analytical utility, the framework is applied to Gojek Indonesia as an illustrative case using publicly available secondary information, without claiming empirical verification or access to proprietary algorithmic processes. The analysis indicates partial alignment between Gojek’s documented initiatives and human-centric principles, particularly in interface transparency, communication design, and worker-support mechanisms, while also exposing persistent tensions related to power asymmetry and limited algorithmic visibility. The study concludes that although secondary evidence suggests opportunities for human-centric implementation, comprehensive evaluation requires multi-method empirical research capable of capturing lived experiences and internal decision-making structures.